Flow and heat transfer characteristics of mist/steam two-phase flow in the U-shaped cooling passage with 60 deg. ribs. (June 2019) - Jiang, Guangwen; Gao, Jianmin; Shi, Xiaojun
Abstract: The flow and heat transfer characteristics of mist/steam coolant in U-shaped gas turbine cooling passage are studied in this paper. The mist/steam mass ratio and mist diameter are carefully analyzed with the numerical method. The results show that the heat transfer of the ribbed-wall gradually increases with the increasing of mist/steam mass ratio. Under the condition of water mist diameter = 10 μm, as mist mass ratio increases from 2% to 10%, the averaged Nusselt number of the First Flow Passage increased by 60.13% and the Second Flow Passage increased by 112.5%. The evaporation rate and surviving time of mist can be controlled by controlling the mists diameter. Larger mist diameter is not always good for enhancing the heat transfer of the ribbed walls. When mist/steam = 8%, as for the First Flow Passage and the Second Flow Passage, water mists of 10 μm diameter has higher average Nu number of ribbed wall than mists of 5 μm, 15 μm and 20 μm. The improvement of the heat transfer performance obtained from the evaporation of the water mist is bound to the increasing of the heat transfer non-uniformity of the heated walls.